Everloft - Lee, Yi Jie (Nanyang Technological University, 2020)
Designed with the environment and eco-sustainability in mind, Everloft attempts to raise awareness on the environmental issues raised by textile production (specifically cotton) and to reduce the impact of fast fashion on global warming by creating an alternative way to handle cotton waste.